The Influence of the Principal's Leadership Style on Teacher Performance and Organizational Culture in Primary Schools Sindangkasih District - Mukhlisin, Ois; Hidayat, Syarip; Elan (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2025)
The purpose of this research is to determine the influence of the principal's leadership style on teacher performance and organizational culture. This research uses a quantitative approach with an explanatory survey method, and the type of data used in this study is primary data. The object of this research is teachers who are ASN (Civil Servants) in Primary Schools located in the Sindangkasih sub-district, with the sampling technique using the saturated sampling method. The data analysis technique used is Structural Equation Modeling (SEM) analysis. The research results show that the influence of the principal's leadership style on teacher performance is 25.1% and the influence of the principal's leadership style on organizational culture is 55.2%.